Understanding sports coaching : The pedagogical, social and cultural foundations of coaching practice - Cassidy, Tania; Jones, Roblyn L.; Potrac, Paul. (London : Routledge, 2004)
Every successful sports coach knows that good teaching and social practices are just as important as expertise in sport skills and tactics. This book fully explores the social, cultural and pedagogical concepts underpinning good coaching practice
Includes bibliographical references and index.
Keywords: Sports coaching; Coaching (Athletics); Coaching (Athletics)--Philosophy; Coaches (Athletics)--Training of